Validation of computational liquefaction for tailings: Tar Island slump - Shuttle, Dawn; Marinelli, Ferdinando; Brasile, Sandro; Jefferies, Michael (Geotechnical research, 2022)
Finite-element analyses using critical state theory proved necessary to understand the development of static liquefaction during three recent large tailing dam failures at Fundao (in Brazil), Cadia (in Australia) and Brumadinho (in Brazil). However, the complexity of these events prevents these analyses being viewed as a complete validation of the methodology. Here the authors evaluate a far simpler case of static liquefaction: the 1974 Tar Island slump (in Canada). This upstream slump involved a rapid drop of 5 m during construction of a 12.5 m high upstream raise over loose tailings. While not a dam stability issue, the event has the attraction for validation of being load-induced, with simple geometry, and with known material properties and in situ state. The computed liquefaction develops from a prior drained condition before propagating rapidly undrained – there are similarities to the video record at Brumadinho (an animation is provided as online supplementary material to illustrate this). A range of scenarios are explored, with the base case of taking reported conditions at face value giving deformations close to those measured. An important aspect was using elastic shear moduli determined by geophysical methods. The analyses were carried out with commercial software (Plaxis) and used critical state theory with largely familiar soil properties measured by standard methods.